Depiction of shared components in flowering pathway and smut whip development pathway in sugarcane - Sehgal, Deepak (2022)
Sugarcane is one of the most valuable industrial and agricultural cash crops, currently being grown in more than 100 countries across the globe, and also contributes significantly to the Brazilian economy. Sugarcane smut disease caused by basidiomycete biotrophic fungi Sporisorium scitamineum is a prominent threat for sugarcane, costing up to 80% of the yield, and in turn, have a major economic impact. Therefore, unraveling components of molecular crosstalk between smut fungi and sugarcane is imperative to find a solution to manage this disease and protect the livelihoods of farmers worldwide. This work aimed to contribute to this cause by understanding the correlation of smut fungi and the flowering pathway in sugarcane. In the first chapter, the current understanding of the flowering pathway in the model plant Arabidopsis thaliana and the correlation between smut fungi with flowering pathways was reviewed. Smut fungi are biotrophic in nature and generally infect grass species, and some of the smut fungi species have been demonstrated to modulate the floral structures of the host plants and interfere with the flowering pathway to survive and reproduce. Since Sugarcane is also a grass species, we hypothesized the existence of a similar mechanism in the sugarcane smut fungi pathosystem. This is why we embarked on this journey to understand this correlation by studying sugarcane- smut interaction at a molecular level by specifically focusing on the components of the flowering pathway. In the second chapter, we used RNASeq to generate transcriptional profiling of smut-resistant (SP80-3280) and smut-susceptible (IAC66-6) genotypes 48 hours after inoculation with smut fungi and also constructed co-expression networks to study the effect of smut fungus infection on the expression levels of putative orthologs of flowering genes in sugarcane. Our data unraveled that the smut fungus elicits an antagonistic expression pattern of flowering genes in two sugarcane genotypes with contrasting levels of smut tolerance. Transcriptional profiling and co-expression networks of the smut resistant genotype suggest the repression of flowering pathway, and on the contrary, the data from the smut-susceptible genotype suggest that smut fungus induces the activation of flowering pathway. Our results also indicated the potential epigenetic regulation at play in the sugarcane-smut pathosystem. Plants, in general, accelerate the floral transitioning process under stress conditions to reproduce before it succumbs to the stress, and our results specifically from the susceptible genotype suggest that potentially, a similar mechanism exists in sugarcane as well. In the third chapter, based on these results, we conducted an exploratory study to evaluate the influence of a known flowering repressor, ethephon, in sugarcane-smut interaction at a physiological and molecular level. No physiological impact on the smut disease progression or whip developmental process was observed due to ethephon treatment in time-points analyzed. The effect of ethephon on candidate flowering genes varied depending on the genotype and the developmental stage. Ethephon seems to potentially have the ability to modulate the expression behavior of candidate flowering genes independently of the fungus as all the candidate flowering genes tested had lower expression levels in ethephon treated samples compared to the untreated ones in the susceptible genotype. For the first time, this study has provided an in-depth analysis of correlation of flowering-related genes in the sugarcane-smut pathosystem. It encourages the idea that the sugarcane smut fungus has the same modus operandi as other smut fungi species to interfere with flowering pathways for its own growth and reproduction purposes. This is the first study in the direction of depicting the shared components in flowering and smut whip development pathways and should encourage more detailed studies in future to unravel all the components in these two distinct genetic pathways. This information will help in finding better management solutions for the smut disease in sugarcane.